Lichen planus pigmentosus-inversus following Langer's lines of cleavage: a rare clinical presentation - Wan-Su Peng; Cheng Tan (Wolters Kluwer Medknow Publications, 2015)
We present an interesting case of a patient who had a 5-month history of insidiously developing pigmented macules along skin cleavage lines over the skin of submammary and inguinal folds. There was no history of previous medication. Skin examination revealed multiple discrete and slate-grey macules distributed over the skin cleavage lines of the submammary and inguinal folds. These lesions did not coalesce, forming several, intermittent and brownish lines. Pathologically, it showed atrophic epidermis with foci of colloid bodies. A dense lymphocytic infiltration along with prominent melanophages was noticeable in the superficial dermis. The patient was diagnosed with lichen planus pigmentosus-inversus following skin cleavage lines.